2015
DOI: 10.1089/ars.2014.6027
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Novel c-Myc-miR27-Prohibitin 1 Circuitry in Cholestatic Liver Injury Inhibits Glutathione Synthesis in Mice

Abstract: Aims: We showed that chronic cholestatic liver injury induced the expression of c-Myc but suppressed that of glutamate-cysteine ligase (GCL, composed of catalytic and modifier subunits GCLC and GCLM, respectively). This was associated with reduced nuclear antioxidant response element (ARE) binding by nuclear factorerythroid 2 related factor 2 (Nrf2). Here, we examined whether c-Myc is involved in this process. Results: Similar to bile duct ligation (BDL), lithocholic acid (LCA) treatment in vivo induced c-Myc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 34 publications
3
67
0
Order By: Relevance
“…C-Myc, which we had shown previously to be induced during BDL [54] and prohibitin 1 (PHB1), a well-known mitochondrial chaperone protein [55], also play important roles in modulating Nrf2-mediated ARE-dependent gene expression. Interestingly, c-Myc is thought to induce PHB1 at the transcriptional level but we found PHB1 expression fell despite the induction of c-Myc during cholestasis [53]. This was a result of c-Myc-mediated induction of miR27a/b, which targets both PHB1 and Nrf2 directly to reduce their expression.…”
Section: Micrornas Targeting Glutathione Synthesis/metabolismmentioning
confidence: 80%
See 2 more Smart Citations
“…C-Myc, which we had shown previously to be induced during BDL [54] and prohibitin 1 (PHB1), a well-known mitochondrial chaperone protein [55], also play important roles in modulating Nrf2-mediated ARE-dependent gene expression. Interestingly, c-Myc is thought to induce PHB1 at the transcriptional level but we found PHB1 expression fell despite the induction of c-Myc during cholestasis [53]. This was a result of c-Myc-mediated induction of miR27a/b, which targets both PHB1 and Nrf2 directly to reduce their expression.…”
Section: Micrornas Targeting Glutathione Synthesis/metabolismmentioning
confidence: 80%
“…Recently we described the involvement of miR-27a and miR-27b in downregulating GCLC and GCLM expression during chronic cholestatic liver injury by mechanisms that involve Nrf2 and a novel co-activator of ARE (Fig. 4) [53]. A variety of in vivo and in cellulo models, including bile duct ligation (BDL), in vivo lithocholic acid (LCA) treatment (gavage daily) and Huh-7 cells treated with LCA were employed.…”
Section: Micrornas Targeting Glutathione Synthesis/metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent report from Yang and colleagues showed that Nrf2 signaling was down-regulated through a c-Myc-miR27a/b-PHB1 circuit. Lithocholic acid (LCA) induced c-Myc and reduced expression of Nrf2 and GCL in mice [370]. c-Myc promoted induction of microRNA 27a/b that targeted both PHB1 and Nrf2 to reduce their expression.…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of c-Myc or miR27a/b attenuated LCA-mediated suppression of Nrf2 and GCL expression. Furthermore, c-Myc directly interacted with Nrf2 and lowered Nrf2 binding to EpRE [370]. Indeed, c-Myc was negatively associated with expression of Nrf2-target genes in various tissues of mice [157, 371].…”
Section: Introductionmentioning
confidence: 99%